0
$\begingroup$

Given $f_{t}=u_{t} - \bar{P}$ and the law of motion for $u_{t} = \rho u_{t-1} + \epsilon_{t}$, where $0<\rho<1$, $\epsilon_{t}$ is mean-zero iid and can be interpreted as a domestic price level shock. .

I want to calculate this difference equation: $s_{t} = (1-\beta)f_{t}+\beta E_{t}s_{t+1}$.

Using Law of Iterated Expectations, I iterate forward by one period and obtain $$s_{t} = (1-\beta) E_{t} \sum_{j=0}^{T} \beta^{j} f_{t+j} + \beta^{T+1} E_{t} s_{t+T+1}$$ $$ s_{t}=(1-\beta) E_{t} \sum_{j=0}^{\infty} \beta^{j} f_{t+j}$$ if $\lim_{T\rightarrow \infty } \beta^{T}E_{t} s_{t+T} = 0$.

Then how do I use the law of motion for $u_{t}$ to solve for $s_{t}$?

$\endgroup$
0
$\begingroup$

By applying the above difference equation on $ s_{t}=(1-\beta) E_{t} \sum_{j=0}^{\infty} \beta^{j} f_{t+j}$, we obtain $$s_{t}=(1-\beta) E_{t} \sum_{j=0}^{\infty} \beta^{j} \left [ \bar{P} - u_{t+j} \right ].$$

The given process for $u_{t}$ implies $E_{t} u_{t+j} = \rho ^{j} u_{t}$. Substituting this result into the previous equation and by using the formula of the geometric sum yields $$s_{t} = \bar{P} - \frac{1-\beta}{1 - \rho \beta} u_{t}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.